2013
DOI: 10.1177/0363546513503288
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Slope and Further Anterior Cruciate Ligament Injuries in the Anterior Cruciate Ligament–Reconstructed Patient

Abstract: An increased posterior tibial slope is associated with increased odds of a further ACL injury after ACL reconstruction. The increased risk is most pronounced in those with a posterior tibial slope of ≥12°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
290
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(322 citation statements)
references
References 34 publications
(39 reference statements)
10
290
6
3
Order By: Relevance
“…The risk for ATT 5 mm was 3.5 times higher in patients with a medial PTS .5.6°than a lateral PTS 5.6°. Similarly, Webb et al 21 reported that a threshold of 12°increased the odds of further ACL ruptures by a factor of 5.2 using lateral radiographs.…”
Section: Discussionmentioning
confidence: 91%
“…The risk for ATT 5 mm was 3.5 times higher in patients with a medial PTS .5.6°than a lateral PTS 5.6°. Similarly, Webb et al 21 reported that a threshold of 12°increased the odds of further ACL ruptures by a factor of 5.2 using lateral radiographs.…”
Section: Discussionmentioning
confidence: 91%
“…35,37 The investigation of the posterior tibial plateau is still pertinent because it has been found that patients with an increased slope have a higher risk of ACL reinjury after ACL reconstruction. 38 Further research should determine the role of tibial plateau depth and meniscal slope in the risk of ACL injury in male patients.…”
Section: Narrow Notch Angle and Acl Injurymentioning
confidence: 99%
“…The key to the development of effective prevention strategies is to identify modifiable risk factors. While some studies report an association between ACL injury and anatomical,7 8 hormonal9 and genetic10–12 components, they are not modifiable in current medical practices. Conversely, biomechanical and neuromuscular components are modifiable.…”
Section: Introductionmentioning
confidence: 99%